Challenges and determinants in the management of the older patients with cancer – Report from a low- and middle-income country - Ramesh Kandel; Joyita Banerjee; Manicka Saravanan; Prasun Chatterjee; Avinash Chakrawarty; S N Dwivedi; Bidhu Kalyan Mohanti; Aparajit Ballav Dey (Journal of the Indian Academy of Geriatrics, 2021)
Introduction: Cancer is a malady of old age. Older people lose autonomy and independence due to age-associated functional decline and adverse consequences of comorbidity. The impact of these variables has an effect on treatment decisions in older cancer patients. Methods: In an observational study, 290 cancer patients aged 60 years or more were evaluated before the initiation of the treatment. They were subjected to a geriatric assessment by various validated assessment tools. Management decisions were as per the prevailing hospital practice. Results: The median age at the diagnosis was 65 years and two-third were males. Lung cancer was the most common (49.3%) diagnosis. The major comorbidities seen were hypertension (34.14%), diabetes (20.34%), and COPD (15%). Depression (57%), cognitive impairment (37%), malnourishment (34%), and vision problem (20%) were common age-related issues observed. Seventy-one percent were dependent in one or more domains of activities of daily living. Eighty-one percent had Eastern Cooperative Oncology Group status score between 0 and 2 (thereby eligible for treatment). In multivariable analysis, good functional status (P < 0.001) and performance status by Karnofsky's Performance Status Scale (P < 0.001) were associated with receiving treatment. Conclusion: Improvement in pretreatment functional status by initial geriatric assessment and requisite interventions may improve the access to and consideration of older cancer patients for standard treatment and care in oncology clinics.